Optimization of Infrastructure and Medical Equipment Application (ASPAK) at Bumi Arjo Health Center Using the HOT-Fit Model - Setria Nur Afifah; Siti Halimatul Munawarah Siti; Iwan Stia Budi; Indah Fasha Palingga (Gaster, 2026)
Background: Technology is vital in improving healthcare quality through effective management of facilities, infrastructure, and medical equipment via the ASPAK system. At Bumi Arjo Health Center, ASPAK performance reached only 41.52%, far below the national target of 60%, indicating the need for optimization. Objective: This study analyzed the optimization of ASPAK implementation at Bumi Arjo Health Center using the HOT-Fit framework (Human, Organization, Technology, and Environment). Method: A qualitative descriptive approach was applied to explore factors influencing ASPAK implementation. Data were obtained through in-depth interviews, observation, and document review with six informants. Credibility was ensured through triangulation of sources, methods, and data. Analysis used content analysis aligned with HOT-Fit dimensions. Result: ASPAK optimization was influenced by several interrelated factors. In the human aspect, limited technical understanding and workload hindered data consistency. Organizationally, leadership supervision and role clarity were essential, though inter-unit coordination remained weak. Technological barriers included system errors, unstable networks, and limited supporting devices. Environmentally, weak cross-sector collaboration and inadequate external support constrained resources. Nevertheless, ASPAK improved documentation quality, data accuracy, and evidence-based planning. Conclusion: ASPAK optimization relies on leadership commitment, inter-sectoral collaboration, and strengthened digital capacity among users. Theoretically, this study refines the HOT-Fit model by highlighting environmental and policy dimensions, while practically providing recommendations to enhance digital health governance in Indonesia’s primary healthcare system.